Michaelina Wautier’s Flower Garland with Butterfly Investigated: Technical Studies as a Source for Scholarship on Early Modern Women - Derks, Kirsten; Janssens, Koen; Van der Stighelen, Katlijne; Van der Snickt , Geert (Early Modern Low Countries, 2025)
While the field of technical art history has progressed tremendously over the last decades, there has been little technical research into paintings made by early modern women artists. As archival and documentary evidence on these women is often scarce, the objects made by them are our best sources for learning more about them as artists. This article explores the potential of this methodology: how can technical examinations of paintings provide us with more information on women artists, and more specifically their studio practice, training, and artistic and professional network? Michaelina Wautier’s Flower Garland with Butterfly serves as a case study. Technical research into this painting revealed a clear technical influence of Antwerp-based specialised flower painters on the materials and painting techniques employed by Wautier. The way Wautier used a lay-in to prepare the composition shows many similarities with a specific painting technique developed and employed by specialised flower painters from Antwerp. Moreover, Wautier’s use of the pigment orpiment shows more of this technical influence from flower painters.